Lucas partitions - Neville Robbins (International Journal of Mathematics and Mathematical Sciences)
The Lucas sequence is defined by: L0=2,L1=1,Ln=Ln−1+Ln−2 for n≥2. Let V(n), r(n) denote respectively the number of partitions of n into parts, distinct parts from Ln. We develop formulas that facilitate the computation of V(n) and r(n).